Turnaround Initiatives and Going Concern Opinion - Chandra Prasadhita (Journal of Applied Business, Taxation and Economics Research, 2021)
The main purpose of this study is to examine the role of Statement on Auditing Standards (PSA) No. 30 which requires an independent auditor to evaluate management actions to overcome the financial distress of the company to reduce the possibility of going concern opinion acceptance. Implementation of turnaround initiatives consists of additional capital, borrowing and debt restructuring, asset sales and cost reduction activities. The population of this research is 454 manufacturing companies listed on Indonesia Stock Exchange during 2011-2013. This study finds that borrowing and debt restructuring are positive information which reduces the probability of receiving going concern opinions. Whereas, cost reduction is the negative information that increases the probability of receiving going concern opinion. That shows there is no significant effect of withdrawal of capital and asset sales activities on the probability of going concern opinion acceptance.